Physical, structural and optical study of erbium oxide doped zinc borosilicate glass substrate for biosensor application - Al-Nidawi, Ali Jabbar Abed (2023)
Glass substrates, with their ultrasonic and enhanced Raman signals, are in high demand for medical applications. Over the past two decades, surface plasmon resonance biosensor technology has made tremendous advancements. However, there are multifaceted gaps in the current state-of-the-art that need to be addressed, with sensitivity being one of the most critical concerns. The poor sensitivity is primarily caused by weak Raman scattering of light. Only a small number of incident photons, around 10-12, scatter, making Raman characterization unrealistic without a significant signal improvement. This fundamental problem with Raman scattering observation needs to be addressed. Several strategies have been proposed to improve the sensitivity of the biosensor, utilizing metal nanoparticles, nanoholes, metallic nano slits and colloidal gold nanoparticles in a buffered solution. However, achieving precise control over the geometry and optical properties of nanostructures remains challenging. Limited research has focused on enhancing the properties of the sensor platform, with only a few studies utilizing Er2O3 doping on the zinc borosilicate glass substrate, along with a thin layer of gold as a platform and a layer of silver nanoparticles. Therefore, this research suggests altering the elastic properties and Raman shifting in the surface plasmon resonance results of the glass substrate, which can be beneficial for optical biosensor applications. The objective of this study is to examine the impact of doping Er2O3 in the B2O3-ZnOSiO2 glass system using the melt quenching technique with specific raw materials. The focus is on characterizing the physical, structural, elastic and optical properties, as well as the SPR results of the glass substrate. The materials' amorphous and glassy characteristics were verified using XRD and FTIR techniques. The ultrasonic method was employed to determine the glass’s ultrasonic longitudinal and shear velocities at a 5 MHz resounding frequency, allowing for the study of elastic moduli. The addition of boron and erbium oxide resulted in increase and decreasing trend for the longitudinal, Young, shear and bulk moduli. Furthermore, the Debye temperature, softening temperature, thermal expansion coefficient and microhardness of the glass framework were evaluated and analyzed using the experimental data. As the boron content increases and acts as a modifier, the number of non-bridging oxygen atoms increases, causing the expansion of the glass network. The energy band gap value increases from 3.25 to 3.54 eV with a boron content increase from 0.10 to 0.20 wt.% and subsequently decreases from 3.48 to 3.43 eV at 0.25 and 0.30 wt.%. Moreover, the main result of this study, increasing the concentration of B2O3 leads to shifting to a high wavelength in the SPR measurement. On another hand, the results from ultrasonic show an increase in the glass rigidity and stability of the glass network with an increase in the concentration of B2O3. From these results can conclude that the best concentration of boron is 0.30 wt.% to prepare zinc borosilicate glass substrate that can be used for biosensors devices. The addition of Er2O3 from 0.01 to 0.05 wt.% to zinc borosilicate glass resulted in a decrease in the energy band gap from 3.28 to 3.23 eV. Moreover, the ultrasonic results demonstrate an increase in the rigidity and stability of the glass network with an increase in the concentration of Er2O3 to 0.04 wt.% using the Otto configuration. Finally, the wavelength shifting observed in the SPR results, approximately 6 nm with gold nanolayer coating and 3-4 nm with silver nanoparticle coating on this glass substrate, can be utilized in the future for constructing integrated silicon-based glass substrates for optical sensors.